HADIS AL-FITRAH DALAM PENELITIAN SIMULTAN - Damanhuri Damanhuri (STAI Ma'had Aly Al-Hikam Malang, 2014)
This simultaneous study on hadith al-Fithr aims to determine the quality and to know the meaning of that hadith. The hadith to be examined is that hadith narrated by Abu Hurayrah which was taken out by al-Bukhari inwhere its chain of narrators are five narrators. In a partial analysis of the results shows that all existing transmitters of the hadith are fully qualified, thiqah, and all transmitters of the respective meet with a narrator's status as a teacher. Matan hadith is apparently not shadh, meaning does not conflict with the arguments naqli both the Qur'an and Hadith with a higher quality linkage. Matan hadith is also not affected by illat, meaning does not conflict with the arguments aqli, either with a healthy mind, senses, history, and science. In simultaneous analysis, it is found that first, the hadith is not able to improve its quality, because it has quality, sahih. Second, these traditions have four shahid, who can increase the degree-quantity. The original tradition of degree was ahad- gharib increased to ahad-mashhur. The conclusion, quality of the hadith of al-Fithr is sahih-mashhur, sahih in quality and mashhur in quantity. The meaning content is that the prophet Muhammad saw teaches a good-active innate pontential of human being.